2016
DOI: 10.1177/0269216316671279
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care education for medical students: Differences in course evolution, organisation, evaluation and funding: A survey of all UK medical schools

Abstract: Development, organisation, course evaluation and funding for palliative care teaching at UK medical schools are variable. This may have implications for delivery of effective palliative care education for medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
(46 reference statements)
2
25
1
2
Order By: Relevance
“…The need to include PC in medical training has been debated in other countries 3. Several studies have been performed to assess the need for this knowledge, the best way to introduce it into the medical school curriculum, and opinions among students and physicians regarding this addition 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…The need to include PC in medical training has been debated in other countries 3. Several studies have been performed to assess the need for this knowledge, the best way to introduce it into the medical school curriculum, and opinions among students and physicians regarding this addition 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of palliative care course organisers, at all 30 UK medical schools, revealed a lack of consistency in the organisation of palliative care education (Walker et al, 2017). Despite this being a core General Medical Council competency, this study indicated that not all schools were adequately preparing medical students to care for patients at the end of their lives.…”
Section: Delivering High Quality End-of-life Carementioning
confidence: 70%
“…However, there are little recent UK data to draw upon (Cavaye & Watts, ), possibly due to the move away from dedicated modules on end‐of‐life care, towards integration across programmes. A survey of palliative care course organisers, at all 30 UK medical schools, revealed a lack of consistency in the organisation of palliative care education (Walker et al, ). Despite this being a core General Medical Council competency, this study indicated that not all schools were adequately preparing medical students to care for patients at the end of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Although most Canadian medical schools offered clinical rotations in palliative care, only a minority of trainees at the undergraduate and postgraduate levels completed such a rotation during their training. The low rate of completion of palliative care rotations is not unique to Canada; it has also been observed in the United Kingdom, 11,12 the United States, 13 Switzerland 14 and Thailand. 15 However, this does not justify the status quo.…”
Section: Discussionmentioning
confidence: 99%